Types and processes of slope movements along East-West Highway, Surai Khola area, Mid-Western Nepal Sub-Himalaya - Tamrakar, Naresh Kazi; Yokota, Shuichiro (Bulletin of the Department of Geology, 2008)
Many landslides and debris flows have occurred and destroyed the East-West Highway that extends along the valley slopes of the Siwalik Hills. Wedge slide, rock fall, slump, rock topple-rock slide, debris flow, slope failures and gully erosion were recorded in the Surai Khola area. The most of the slope movements distributed therein are active, reactivated and retrogressive. Differential weathering and gully erosion related to bedding planes of rocks are common phenomena, which contribute instability. The areas between Surai Naka and the Chor Khola suffer remarkable uplift, tilting and river incision, and thus indicate tectonically active zone. Tectonic activity, lithological assemblage, rock strength and weathering of the Siwalik Group have remarkable input on distribution, causes and activity of slope movements.   doi: 10.3126/bdg.v11i0.1427        Bulletin of the Department of Geology, Tribhuvan University, Kathmandu, Nepal, Vol. 11, 2008, pp. 1-4